Pharmacy Compounding Regulation in the German Pharmaceutical Market. Part 1. Basic Regulatory Provisions (Review) - S. E. Erdni-Garyaev; D. D. Mamedov; D. S. Yurochkin; D. D. Zelikova; Z. M. Golant; V. S. Fisenko; I. A. Narkevich (Регуляторные исследования и экспертиза лекарственных средств, 2024)
SCIENTIFIC RELEVANCE. There is a need to move towards an appropriate system of quality assurance in pharmacy compounding. At the same time, the development of a Russian regulatory system for pharmacy compounding requires a broad understanding of international experience.AIM. This study aimed at analysing the basic principles of pharmacy compounding regulation in the Federal Republic of Germany in order to identify best practices and determine ways to improve the legal and regulatory framework for compounding pharmacies in the Russian Federation.DISCUSSION. According to German law, pharmacies may dispense compounded medicinal products on an oral request from a patient. The German regulatory framework provides a mechanism delineating medicinal products compounded by pharmacies and those manufactured by pharmaceutical companies. The geographical and quantitative restrictions combined with the neutral pricing policy for pharmacies facilitate the establishment of a highly effective pharmaceutical supply system. In practice, this system helps set uniform prices for medicinal products throughout Germany while preventing pharmacy chains from monopolising the pharmaceutical market. These regulations can be considered regulatory mechanisms operating at the regional (land) level. Moreover, it is of key importance that German legislation divides compounded medicinal products into stock and extemporaneous preparations.CONCLUSIONS. German pharmaceutical practice features a number of innovations that can be borrowed for Russian pharmaceutical practice. Russian pharmaceutical legislation may benefit from adopting the concept of a “request from an individual” for dispensing compounded medicinal products that do not contain prescription-only active pharmaceutical ingredients (APIs). In order to improve the efficiency of the use of pharmaceutical-quality raw materials, including APIs, it is necessary to identify cases in which regular pharmacies can receive or purchase compounded medicinal products from compounding pharmacies and cases in which compounding pharmacies can purchase APIs from other compounding pharmacies. The authors recommend considering the possibility of defining the role, functions, and powers of self-regulating professional pharmacy organisations at various levels of governance in this social sphere of activity. Furthermore, the authors recommend creating a Russian mechanism to mitigate the risks of stock shortages and/or limited supply of medicinal products that would be similar to the German “standard authorisation” system and would encompass compounding pharmacies and pharmaceutical companies.